GPs’ awareness of car driving among oldest patients: exploratory results from a primary care cohort - Leve V; Pentzek M; Fuchs A; Bickel H; Weeg D; Weyerer S; Werle J; König H-H; Hajek A; Lühmann D; van den Bussche H; Wiese B; et al. (Royal College of General Practitioners, 2021)
Background Increasingly more very old people are active drivers. Sensory, motor and cognitive limitations, and medication can increase safety risks. Timely attention to driving safety in the patient–doctor relationship can promote patient-centred solutions. Aim To explore the following questions: do GPs know which patients drive a car? Is fitness to drive addressed with patients? Design & setting Cross-sectional data from patient interviews and GP survey in the ninth follow-up phase of a prospective primary care cohort (the German Study on Ageing, Cognition and Dementia in Primary Care Patients (AgeCoDe) and the Study on Needs, Health Service Use, Costs and Health-Related Quality of Life in a large sample of ‘oldest-old’ primary care patients (≥85 years; AgeQualiDe)) . Method The sample consisted of patients in the age group ≥85 years and their GPs. Independent reports were gathered on driving activity from the GP and the patient, and information was gained from GPs on whether driving ability was discussed with the patient. Statistical analyses included validity parameters and bivariate characterisation of subgroups (non-parametric significance tests, effect size). Results Self-reports of 553 patients were available (69.5% female; mean age 90.5 years; 15.9% drive a car). For 427 patients, GP data were also available: GPs recognised 67.1% correctly as drivers and 94.9% as non-drivers. GPs said that they had discussed fitness to drive with 32.1% of potentially driving patients. Among drivers who were not recognised and with whom driving had not been discussed, there were more patients with a low educational level. Conclusion The GP’s assessment of driving activity among very old patients showed moderate sensitivity and good specificity. Driving ability was seldom discussed. Asking an appropriate question during assessment could increase GPs’ awareness of older patients’ automobility.
Keywords: aged, 80 and over; automobile driving; clinical decision-making; general practice; physician—patient relations; validity